GIS-Based flood prediction of the Black Volta in a climate change scenario. case study:the Dikpe catchment in the Lawra District of the Upper West Region - Danquah, Twumasi Yaw (2016)
A thesis submitted to the Department of Geometric Engineering, Kwame Nkrumah University of Science and Technology in partial fulfillment for the degree of Master of Science, 2013